The Realization of Communication Strategies Used by Extrovert and Introvert Students in Conversation - Mujahadah, Siti; Rukmini, Dwi; Faridi, Abdurrachman (Universitas Negeri Semarang, 2018)
This research aimed to analyse and explain the realization of communication strategies by extrovert and introvert students in conversation. The subject was the fourth semester students in Walisongo State Islamic University. This research employed the descriptive qualitative. I used questionnaire to determine the students’ personality. Recording is needed to obtain the data then followed by transcribing and analyzing the data. The result reveals that extrovert students realized four kinds of communication strategies and do introvert. The similarities were found in the percentage rating of realization which stalling or time-gaining strategies was most used in the conversation. Students tended to use this strategy to maintain the conversation. The next similarity was the way of their realization of communication strategies. They also used those strategies for the same purpose and function. For the differences between extrovert and introvert students, it was found that frequency of the realization was different. The extrovert students tended to more dominant in all strategies than introvert. It showed that extrovert students often used achievement strategies, stalling or time-gaining strategies, and self-monitoring strategies than introvert. In interactional strategies, the introvert tended to use interactional strategies more often than extrovert.